Ecotourism as A Soft Skill Practice for Millenials - Satrya, I Dewa Gde; Kaihatu, Thomas Stefanus; Pranata, Lexi (Universitas Ciputra Surabaya, 2019)
Traveling not only creates fun for tourists. Tourism activities are believed to also improving human resources ability. It is a significant aspect related to human resource capacity that soft skills ownership which can be trained to modern travellers through ecotourism activities. This descriptive qualitative study describes soft skills trained to tourists from among younger generation in ecotourism destinations. Statement of the problem in this research is what is the relevance between ecotourism and soft skill ownership? This study identifies soft skills trained in ecotourism activities that are interpersonal skills characterized by communication skills, like others, have empathy and concern, warm, forgiving, open, adaptive and self-control abilities. The interpersonal skills that are part of this soft skill are believed to be important and will help younger generation to succeed in living their lives.